Exploring Experiences with Sterilization among Nulliparous Women - Shreffler, Karina M. (Womens Reprod Health (Phila), 2020)
Although nulliparous women who are sterilized appear voluntarily “childfree,” the majority report non-contraceptive reasons for their surgical procedure. Using an analytical subsample of the National Survey of Fertility Barriers, we examined 105 women’s closed- and open-ended responses about the reasons for their sterilization surgeries and whether their sterilization occurred before their childbearing desires were met. We found considerable heterogeneity in the experiences and attitudes of participants. We highlight important implications of women’s experiences for fertility and reproductive health research and practice, particularly by drawing a distinction between voluntarily childfree and involuntarily childless women.